Altitude Training Conference Northern Arizona University Flagstaff, Arizona March 1998
ALTITUDE TRAINING CONFERENCE NORTHERN ARIZONA UNIVERSITY FLAGSTAFF, ARIZONA MARCH 1998 Report Slides Presentations - Jay Kearney & Randy Wilber Optimum Utilisation of Altitude Training - the High-Low Model Optimal Altitude for Maximising Human Powered Cycle Speed Altitude Training and Endurance Performance Determinants of Maximal Oxygen Utilisation Conclusions Recommendations List of Altitude Training Centres visited